Respuesta :

Answer:

Step 1: Simplify both sides of the equation.

5x+1=6x−x

5x+1=6x+−x

5x+1=(6x+−x)(Combine Like Terms)

5x+1=5x

5x+1=5x

Step 2: Subtract 5x from both sides.

5x+1−5x=5x−5x

1=0

Step 3: Subtract 1 from both sides.

1−1=0−1

0=−1

Answer:

There are no solutions.

 

Step-by-step explanation:

Answer:

no solution

Step-by-step explanation:

Given

5x + 1 = 6x - x , that is

5x + 1 = 5x ( subtract 1 from both sides )

5x = 5x - 1 ( subtract 5x from both sides )

0 = - 1 ← not possible

This indicates the equation has no solution